Unidentified person using a Spinco Physiological Gas Analyzer
It is unclear from this photograph whether this is a Model 150 or 160.
Keywords: Beckman Instruments, Inc. Spinco Division; Gases--Analysis; Scientific apparatus and instruments; Beckman Instruments, Inc.